2008
DOI: 10.1089/jamp.2007.0656
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Chemotherapy

Abstract: Regional chemotherapy has been proposed as a treatment modality in a number of cancer settings. In primary or metastatic lung cancer, administration of chemotherapy via inhalation could increase exposure of lung tumor to the drug, while minimizing systemic side effects. Several proof of concept studies in animal models of metastatic or primary lung cancer have demonstrated the safety, pharmacokinetic advantage, and antitumor effect of aerosol administration of several chemotherapeutic agents including doxorubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 38 publications
4
53
0
Order By: Relevance
“…Other chemotherapeutic agents also administered aerolised were paclitaxel, docetaxel, cisplatin, 5-fu, and doxorubicin. In these studies less systematic side-effects were observed [31,33,36,38,54,58,68]. All patients were decided to be chemo naïve, since patients undergoing 2nd line treatment would be under the influence of the first line systemic toxicities and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other chemotherapeutic agents also administered aerolised were paclitaxel, docetaxel, cisplatin, 5-fu, and doxorubicin. In these studies less systematic side-effects were observed [31,33,36,38,54,58,68]. All patients were decided to be chemo naïve, since patients undergoing 2nd line treatment would be under the influence of the first line systemic toxicities and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of factors that affect the efficacy and bioavailability of aerolised drug formulation [22,57,58,71,72]. These factors are summarized: 1) Aerosol particle size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalization of particles offers an exciting tool to make MNPs target-specific and increase their therapeutic benefit [10]. A successful delivery of magnetic nanoparticle-loaded drugs in the liver [11,12], brain [13], ovarian [11] or in the lung [14] cancer has been already reported.…”
mentioning
confidence: 99%
“…The HEL 12469 cells are human diploid (embryo) lung fibroblasts; these cells were used as a model of normal (healthy) tissue. We selected the human pulmonary cells because the lungs are the target organ by both occupational and public exposure to nanoparticles [18] and the inhalation therapy is a prospective non-invasive curative modality of lung cancer and other lung illnesses [14,19]. Inhalation therapy offers several advantages over systemic treatment.…”
mentioning
confidence: 99%